Militarisation, the state of exception, and fascism in South African universities - Reinders, Michael Bongani (Acta Academica: Critical views on society, culture and politics, 2019)
The militarisation of university campuses in South African has led to the promotion of the use of violence and force against students. During the national student protests in 2015-2017 university management and the South African Police Service (SAPS) used militarisation and force which perpetuated violence on campuses. By understanding the state of exception as the suspension of the rule of law it is evident that it can be used as a fascist way to react to those questioning the status quo. Many South African universities, particularly the University of Pretoria (UP), employed this as a tool to deal with student protests. This shows that South African universities have fascist tendencies when dealing with student protests.